Deciphering the interplay between tectonic and climatic forces on hydrologic connectivity in the evolving landscapes - Han, Kyungdoe; Wilson, John L. (Frontiers in Water, 2024)
The intricate interplay between climate and tectonics profoundly shapes landscapes over time frames surpassing 10 million years. Active tectonic processes and climatic shifts unsettle established drainage systems, instigating fragmentation or amalgamation of watersheds. These activities yield substantial transformation in surface hydrologic connectivity, thereby underlining the profound influence of these tectonic and climatic forces on the evolution of both landscape and hydrology. Such transformations within the hydrological landscape have direct implications for the evolution of aquatic species. As connections among aquatic habitats undergo reconfiguration, they incite shifts in species distribution and adaptive responses. These findings underscore the role of tectonics and climate in not only sculpting the physical landscape but also steering the course of biological evolution within these dynamically changing aquatic ecosystems relying on hydrologic connections. Despite the significance of these interactions, scholarly literature seldom examines alterations in hydrologic connectivity over tectonic, or orogen-scale, timescales. This study aims to bridge this gap, exploring changes in hydrologic connectivity over extended periods by simulating a continental rift system akin to the Rio Grande Rift, USA, subject to various tectonoclimatic scenarios. Multiple rift basins hosting large lakes, brought into existence by active tectonic extension, are further molded by tectonic extension and post-rift climatic changes. The study focuses on phenomena such as interbasin river breakthroughs and knickpoint generation, assembling a time-series of connectivity metrics based on stream network characteristics such as flow rate, flow distance, and captured drainage areas. We anticipate that the insights gleaned from this study will enhance our comprehension of the enduring impact of tectonic and climate processes on hydrologic connectivity and the subsequent evolution of aquatic species.